2011
DOI: 10.1063/1.3571458
|View full text |Cite
|
Sign up to set email alerts
|

Existence of optical phonons in the room temperature ionic liquid 1-ethyl-3-methylimidazolium trifluoromethanesulfonate

Abstract: The technologically important properties of room temperature ionic liquids (RTILs) are fundamentally linked to the ion-ion interactions present among the constituent ions. These ion-ion interactions in one RTIL (1-ethyl-3-methylimidazolium trifluoromethanesulfonate, [C(2)mim]CF(3)SO(3)) are characterized with transmission FTIR spectroscopy and polarized attenuated total reflection (ATR) FTIR spectroscopy. A quasilattice model is determined to be the best framework for understanding the ionic interactions. A no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Dipolar coupling theory 14 has been previously used to relate the magnitude of the TO-LO splitting to the dipole moment derivatives of vibrational modes in a variety of isotropic and anisotropic crystals 1517 , disordered salts 18,19 , and molten salts 8,19 . A simplified form of dipolar coupling theory results in the following expression for the TO-LO splitting of a normal mode in a unimolecular unit cell: 16 …”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dipolar coupling theory 14 has been previously used to relate the magnitude of the TO-LO splitting to the dipole moment derivatives of vibrational modes in a variety of isotropic and anisotropic crystals 1517 , disordered salts 18,19 , and molten salts 8,19 . A simplified form of dipolar coupling theory results in the following expression for the TO-LO splitting of a normal mode in a unimolecular unit cell: 16 …”
Section: Experimental Methodsmentioning
confidence: 99%
“…The dipole moment derivative for a particular vibrational mode may be determined by integrating the extinction coefficient data, 8 …”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…PILs with more delocalized chargesa nd fewer ionic interactions are expected to exhibit higher conductivities. [35,36] In ILs, ion-ion interactions (strong short-range cohesive forces) give rise to long-range, correlated ion motion,w hich is responsible for ion transport. As ac onsequence, PILs with shorter alkyl chains (lowerm olecular weights) exhibit higherc onductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The ionic conductivity of PILs is also known to decreasea st he size of the cation is increased and becomes less mobile. Attempts to shed some light onto this issue by means of infrared spectroscopy were proposed by Burba et al [35,36] These authors concluded that in the presence of large anions and asymmetrical imidazolium cations, ILs exhibit low degrees of charge ordering. Although the literature suggestst hat the trendso bserved for anions are less clear, [31] in the present study this effect is not relevant,a st he two PILs under analysis contain the same anion.…”
Section: Introductionmentioning
confidence: 99%